Risk Profiling In Vitro Fertilization Pregnancies that Develop Placenta Accreta Spectrum - Modest, Anna M.; Einerson, Brett D.; Nieto, Albaro J.; Shrivastava, Vineet K.; Shamshirsaz, Alireza A.; Shainker, Scott A.; on behalf of the Pan American Society for Placenta Accreta Spectrum (American Journal of Perinatology, 2024)
Objective The objective of this study is to assess whether, among a cohort of placenta accreta spectrum (PAS) patients, antenatal suspicion of PAS was less likely in in vitro fertilization (IVF) compared with non-IVF patients. In addition, we aimed to assess whether IVF patients exhibited similar risk factors for PAS compared with non-IVF patients.Study Design This is an international multicenter retrospective study of patients with pathologically confirmed PAS (accreta, increta, percreta) between 1998 and 2021. PAS patients were identified through a central international PAS database. Antenatal and pathological criteria are specific to each institution. Pregnancies that resulted from IVF were compared with non-IVF pregnancies. Comparisons were made using a chi-square or Fisher's exact test for categorical variables and Wilcoxon rank-sum test for continuous variables.Results Of the 692 pregnancies included, 44 were in the IVF group and 648 were in the non-IVF group. The IVF group was less likely to have had a prior cesarean delivery (70.5 vs. 91%, p < 0.01) but a similar prevalence of placenta previa (63.6 vs. 68.1%, p = 0.12) compared with the non-IVF group. The IVF group was also less likely to have either a prior cesarean delivery or placenta previa than the non-IVF group (79.5 vs. 95.4%, p < 0.01). Antenatal detection of PAS was less common in the IVF group compared with the non-IVF group (40.9 vs. 60.5%, p < 0.01, respectively), even when adjusted for maternal age, prior cesarean delivery, prior uterine surgery, placenta previa and site (risk ratio: 0.70, 95% confidence interval: 0.62–0.81). The IVF group had less severe pathological disease compared with the non-IVF group (p = 0.02).Conclusion Pregnant people with PAS who underwent IVF are less likely to have an antenatal suspicion compared with non-IVF patients. This finding may be explained by the lower incidence of prior cesarean deliveries and/or placenta previa as well as less severe forms of PAS.Key Points
Keywords: IVF; PAS; antenatal suspicion